2022
DOI: 10.48295/et.2022.87.4
|View full text |Cite
|
Sign up to set email alerts
|

Residential Density and Traffic Congestion in the Harare Metropolitan Region

Abstract: This study sought to establish the relationship between residential density and traffic congestion. The study adopted a cross-sectional survey design and a mixed method approach. Data was collected from 384 households in Harare Metropolitan Region using structured questionnaires and semi-structured interviews. Structural Equation Modelling was used to test the relationship among residential density, vehicle miles travelled and traffic congestion. The findings revealed that there is a direct relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…This suggests that traffic congestion is influenced by factors such as vehicle miles traveled, number of vehicle trips generated, vehicle ownership, and mode choice. These findings align with findings by Kanyepe et al (2022c), who observed that traffic congestion in Harare is primarily caused by an increase in vehicle ownership, which is exacerbated by the influx of second-hand vehicles. Thus, H3 was accepted.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that traffic congestion is influenced by factors such as vehicle miles traveled, number of vehicle trips generated, vehicle ownership, and mode choice. These findings align with findings by Kanyepe et al (2022c), who observed that traffic congestion in Harare is primarily caused by an increase in vehicle ownership, which is exacerbated by the influx of second-hand vehicles. Thus, H3 was accepted.…”
Section: Discussionsupporting
confidence: 91%
“…Like most African countries, the urban planning frameworks in Zimbabwe were mainly designed to cater to the capitalist and selfish interests of the settler community. Although transport and urban settlement plans are under the purview of metropolitan councils, little attention has been given to upgrading and improving the transportation system within the context of integrated land use and transport planning (Kanyepe et al, 2022b). Despite the rapid growth of cities in terms of population and spatial dimensions, urban roads are grossly inadequate to meet the mobility needs of city dwellers, reflecting a lack of proper coordination between transport and land use plans (Marondedze & Schütt, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Lockstrom (2023) observed that partners who share information can align their cooperative goals to leverage synergies and effectively manage lead-time variabilities resulting from environmental factors. Information sharing enhances coordination and reduces lead times by ensuring the availability of inventory when needed, thereby improving firm performance (Kanyepe, 2022). Additionally, information sharing enables faster responses to demand fluctuations or supply disruptions and helps identify and mitigate risks associated with longer lead times (Ivanov and Dolgui, 2021).…”
Section: H1b the Preprocessing Lead Time Has A Positive Effect On Per...mentioning
confidence: 99%